2019
DOI: 10.1039/c9cc03331a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and regioselectivity of the anionic oxidative rearrangement of 1,3-diketones towards all-carbon quaternary carboxylates

Abstract: The oxidative rearrangement of 1,3-diketones is an underexplored alternative to enolate chemistry in the synthesis of all-carbon quaternary carboxylates. Mechanistic understanding enabled the discovery of a faster and more effective reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Owing to the presence of the conjugated system, IIa presents a redshift absorbance up to the visible region (450 nm), while the absorbance of IIIg / IVg is confined below 400 nm. In situ monitoring of the reaction evolution by semicontinuous 1 H NMR 15 revealed that the catalytic intermediates IIa and IIIg / IVg are the corresponding catalytic resting states. Therefore, the presence of these species in significant concentration during the reaction course along with their absorbance profiles makes them susceptible to further light-triggered processes.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the presence of the conjugated system, IIa presents a redshift absorbance up to the visible region (450 nm), while the absorbance of IIIg / IVg is confined below 400 nm. In situ monitoring of the reaction evolution by semicontinuous 1 H NMR 15 revealed that the catalytic intermediates IIa and IIIg / IVg are the corresponding catalytic resting states. Therefore, the presence of these species in significant concentration during the reaction course along with their absorbance profiles makes them susceptible to further light-triggered processes.…”
Section: Resultsmentioning
confidence: 99%
“…Decarboxylative radical addition reactions ( Scheme 1 A) have recently emerged as prime tools to create aliphatic ligations in biomolecules. 8 , 9 These methods take advantage of the abundance of carboxylic acids 8 , 10 and the various technologies developed with Michael acceptors. 1b , 11 Despite their success, radical addition reactions are slow (6–12 h) and require additional catalysts, inorganic reducing suspensions, and/or additives that are not native to biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Total synthesis has been a major resource to facilitate the supply of scarce substances and a fertile playground to create and test new chemistries . Despite the dominance of natural product and pharmaceutical targets in these studies, our group and others have used ligands to inspire synthetic innovations . The synthesis of metal catalysts offers uncharted opportunities for basic research in both organic and inorganic chemistry and can facilitate the introduction of state-of-the-art catalysts in industrial production.…”
mentioning
confidence: 99%